2021
DOI: 10.3390/ijerph182413336
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Self-Reported Access to Assistive Technology Using the WHO Rapid Assistive Technology Assessment (rATA) Questionnaire: Protocol for a Multi-Country Study

Abstract: In 2018, the World Health Assembly adopted a resolution on improving access to assistive technology (AT), and mandated the WHO to prepare a global report on assistive technology based on the best available evidence and international experience. As limited data on access to AT at country and global levels were available, there was a need to conduct representative population surveys in order to inform the development of the global report, national AT programs, and global initiatives. The objective of this protoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 5 publications
0
15
0
Order By: Relevance
“…Future research could consider asking participants about reported functional difficulties without assistance/APs as well which collects important quality of services data. The WHO Rapid Assessment of Assistive Technology [ 51 , 52 ] uses the WG Short Set with this modification and includes an additional survey section which asks about broader AP use; however, this sole modification generates non-comparable WG functioning data so is not a viable approach.…”
Section: Discussionmentioning
confidence: 99%
“…Future research could consider asking participants about reported functional difficulties without assistance/APs as well which collects important quality of services data. The WHO Rapid Assessment of Assistive Technology [ 51 , 52 ] uses the WG Short Set with this modification and includes an additional survey section which asks about broader AP use; however, this sole modification generates non-comparable WG functioning data so is not a viable approach.…”
Section: Discussionmentioning
confidence: 99%
“…Self-report assessment is typically lower cost, quicker and requires fewer human resources compared to clinical assessment (Boggs et al, 2019(Boggs et al, , 2020. It also, importantly, incorporates consumer choice, and individuals' understanding of their need, uptake and benefit from AT which is crucial for developing AT services (Zhang et al, 2021). However, there are limitations of this approach, with evidence suggesting it can both under-and over-estimate AT need (Mactaggart, Kuper, Murthy, Oye & Polack, 2016;Boggs et al, 2019Boggs et al, , 2020Boggs et al, , 2021bBoggs, Polack, Kuper & Foster, 2021c).…”
Section: Strengths and Limitations Of The Survey Toolmentioning
confidence: 99%
“…When clinical information and problem solving are lacking, and AP awareness is limited, it may be challenging for people to know which factors to consider in self-assessing for APs. The rATA does recommend use of an AP image booklet to enhance participants' understanding of specific APs (Zhang et al, 2021). However, self-assessment of AT need is still challenging and particularly for less familiar APs (e.g., Hearing…”
Section: Strengths and Limitations Of The Survey Toolmentioning
confidence: 99%
See 2 more Smart Citations